Adopting the euro in post-communist countries: An analysis of the attitudes toward the single currency - Miriam S. Allam; Achim Goerres (Max Planck Institute for the Study of Societies, 2008)
The new EU member states in Central and Eastern Europe achieved an economic and political tour de force on their way to EU accession. Their next challenge is the entry to the eurozone. Thus, the dynamics of public opinion toward the euro become crucial for political leaders. We test three perspectives - economic, political, and historical-ideational - with individual-level survey data from eight countries and conclude that the combined model best explains variations in support for the euro. In an environment of volatility in post-communist Europe, macro variables of economic and historicalideational factors have the strongest impact on individual attitudes, while micro-variables of economic self-interest do not further our understanding of euro support. Thus, distributional issues matter less than the aggregate national performance and experience. Political parties that garner support for the euro should therefore concentrate on economic consolidation and political stability rather than politicizing a winner-loser cleavage.
Keywords: 300; Euro; Währungsumstellung; Meinung; EU-Staaten (Osteuropa)